Sex and the supremacy of Christ - Piper, John; Taylor, Justin (Wheaton Crossway Books, 2005)
Book summary: The Bible has a way of shocking us. If Americans could still blush, we might blush at the words, "Rejoice in the wife of your youth, a lovely deer, a graceful doe. Let her breasts fill you at all times with delight; be intoxicated always in her love" (Proverbs 5:18-19). But, of course, sin always tries to trash God's gifts. So we can't just celebrate sex for what God made it to be; we have to fight what sin turned it into. The contributors to this unique volume encourage you to do both: celebrate and struggle. This book has something for allmen and women, married and single from contributors like John Piper, C.J. and Carolyn Mahaney, Mark Dever, Al Mohler, Carolyn McCulley, and others. Included is a DVD with material from the Desiring God national conference, "Sex and the Supremacy of Christ," held in Minneapolis in 2004.
Keywords: Sex -- Religious aspects -- Christianity. RELIGION -- Christian Life -- Social Issues. RELIGION -- Christianity -- General